Stakeholders’ Perception of Skill Adequacy of Vocational Training Component of a University of Education in Southwestern Nigeria - Ojo, Abiodun Adebowale; Ajayi, Olufemi A. (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The trend of high rate of youth unemployment and underemployment, most especially the graduates in Nigeria appears to have defied solution, several social reforms and economic initiatives of the government notwithstanding. Thus, this study sought to investigate stakeholders’ perception of skill adequacy of vocational training component of a University of Education in Southwestern Nigeria. One research question with three hypotheses were generated for the study. The study adopted a descriptive survey design. The sample comprises 504 students of 300 level, 58 lecturers and 61 senior members of non-academic staff. Questionnaire on Stakeholders’ Perception of Students’ Acquisition of Vocational Skills (QSPSAVS) (r=.84) was used in data collection. Data collected were analysed using mean, standard deviation, t-test and ANOVA. The results indicate that stakeholders’ perception (Grand Mean = 2.96) of the adequacy of vocational skills acquired by the student trainees was high. Meanwhile, differences in perception of adequacy of skills acquired by the student trainees based on type of stakeholders (F 2,497 =.391; p (.676) ˃.05) and gender (t= –1.753; p (.080) ˃.05) were not significant. Further, there is no significant interaction influence of category of stakeholders and gender (F 2,493 = 1.490; p (.226) ˃.05) on perception of adequacy of the skills acquired by the student trainees. In conclusion, all the stakeholders were of similar views that the vocational training component of teacher education programme in the University was worthwhile. Thus, the University management should foster the sustainability of the intervention amongst other recommendations. Keywords: Stakeholders’ perception, skill adequacy, vocational training, gender, University of Education